The Number of Mushafs Attributed to The Caliph Uthman - Hasankhon Abdumajidov (Penerbit Jurnal Indonesia, 2024)
The article examines the number of Mushaf of Uthman and the countries to which they were sent. It also surveys on the sources on a relevant topic and provides conclusions drawn